A review of solifenacin in the treatment of urinary incontinence - Ramandeep Basra; Con Kelleher (Dove Medical Press, 2008)
Ramandeep Basra, Con KelleherDepartment of Gynaecology, Guys and St Thomas NHS Foundation Trust, London, England, UKAbstract: Overactive bladder (OAB) is a prevalent condition which has an adverse effect on quality of life. The presence of urgency incontinence confers significant morbidity above and beyond that of OAB sufferers who are continent. The primary treatment for OAB and urgency incontinence is a combination of behavioral measures and antimuscarinic drug therapy. The ideal antimuscarinic agent should effectively relieve the symptoms of OAB, with the minimum of side effects; it should be available as a once-daily sustained release formulation and in dosage strength that allows easy dose titration for the majority of sufferers. Solifenacin succinate was launched in 2005, and has been shown in both short and long term clinical trials to fulfill these requirements. Solifenacin is a competitive M3 receptor antagonist with a long half-life (45–68 hours). It is available in two dosage strengths namely a 5 or 10 mg once-daily tablet. The efficacy and tolerability of solifenacin for the treatment of all symptoms of OAB has been evaluated in a number of large, placebo controlled, randomized trials. Long-term safety, efficacy, tolerability and persistence with treatment have been established in an open label 40 week continuation study.Keywords: solifenacin, urinary incontinence, overactive bladder